(untitled) (Revista Apotheke, 2021)
This article is a reflection of artistic and pedagogical experiences, where exploratory interventions, based on the Dance-Physical Education Method (MDEF), were used as investigative mottos for body awareness of children and adolescents living in the outskirts of the city of Natal (RN). In this way, we aim to contribute to the expansion of their artistic and bodily repertoires, whose cultural and interdisciplinary exchange was carried out by Ação na Comunidade, being a research, teaching and extension project of the Escola de Música da UFRN. The article seeks to erect tripods of dialogue between educational practices, creative processes and scenic communications, which benefit the community in general